Subculture of female Korean culture fans: pleasure, creativity, and sisterhood - Novaria Maulina; Yuyun Wahyu Izzati Surya; I.G.A.K. Satrya Wibawa (Faculty of Communications Science, Dr. Soetomo University, 2024)
The entry of the Korean wave in the early 2000s in Indonesia, which was facilitated by internet technology, has become part of communication activities. This has led to the formation of subcultures of fans of Korean wave products, namely K-Drama and K-Pop, including women's subcultures who like K-drama and K-Pop. This subculture was built and developed through social media such as Facebook and WhatsApp. This article reviews how the digital era has changed how female fans interact to empower themselves through subcultures in the online space, mainly focusing on female fans of K-pop bands and K-dramas. Using the ethnographic research method, the research results show that along with the digital era that continues to develop, the subculture of female fans, initially formed through a physical collective group, has now evolved into a subculture of female fans formed through internet-based interactions. The subculture of female fans in the online space has become a forum for exploring pleasure, creativity, and self-empowerment through text production and reproduction of media texts supported by digital technology. Exploration of fun, creativity, and self-empowerment merged in a sense of sisterhood, participatory and collaborative culture.